Assessing the Effectiveness of Multimodal Text-Based Whole-Language Learning Materials for Children - Ika Yatri; Nur Latifah; Mimin Ninawati (STAI Hubbulwathan Duri, 2024)
Whole Language is a teaching approach emphasizing the natural process of language acquisition, integrating reading, writing, speaking, and listening. This study addresses the need for Whole Language-based teaching materials that utilize multimodal texts to enhance Indonesian language learning for grade IV elementary students. This research developed and validated teaching materials based on the Whole Language approach. The materials incorporate steps such as Reading Aloud, Journal Writing, Sustained Silent Reading, Shared Reading, Guided Reading, Guided Writing, Independent Reading, and Independent Writing. A sample of grade IV students from West Jakarta was selected via simple random sampling. Validation involved three experts assessing material content, language, and media quality using Aiken's V. Validation scores were Aiken V = 0.75 (moderate) for material content, 0.86 (high) for language, and 0.83 (high) for media. These results indicate that the materials meet quality standards and are suitable for enhancing student engagement and comprehension. Findings demonstrate that Whole Language-based materials provide meaningful improvements in reading comprehension, motivation, and critical thinking skills. By emphasizing integrated skills and real-world contexts, these materials offer a holistic and effective learning experience. Whole Language-based teaching materials have the potential to significantly improve language learning outcomes and character education. Their implementation in classrooms can create a more engaging and meaningful learning environment, fostering both academic and personal growth in students.